Biologic and genomic characterization of a novel virulent Aeromonas hydrophila phage phiA051, with high homology to prophages - Wang, Yuzhi; Tong, Guixiang; Jiang, Xinglong; Tu, Chuandeng; Cai, Hongjiao; Fang, Wenhong; Tan, Honglian; Weng, Qibiao; Wei, Xinxian; Lin, Mao (Frontiers in Veterinary Science, 2024)
In this study, a novel virulent Aeromonas hydrophila phage designated phiA051 has been isolated from aquaculture water and identified from biological and genomic perspective. Electron microscopic observation showed that the phage phiA051 was composed of an icosahedral capsid with an isometric diameter of 71.3±2.0 nm, and a tail with length of 73.1±2.7 nm. The phage phiA051 possesses an optimal multiplicity of infection (MOI) of 0.01, and its burst size was 108 PFU/cell. The phage maintained a high viability at temperatures of 30-50℃ or pH 6.0-10.0 for 1 h. Inhibitory capacity against A051 showed that the phage phiA051 has certain potentials in rapidly inhibiting the spread of pathogen early in the outbreak. The whole-genome sequencing revealed that phage phiA051 had a linear dsDNA with GC content of 60.55% and a total length of 32,212 bp, including 46 ORFs. The phage phiA051 behaved as a virulent phage. However, the BLASTN result showed that 23 of the top 25 hits were genomes of Aeromonas strains. It was suggested that phiA051 was probably derived from some prophage in the chromosome of Aeromonas. Further investigation